Research and Development of Self-Contained Water Injection Systems - Bazala, Jiri; Hébert, Guillaume; Fischer, Oliver; Nothbaum, Jürgen; Thewes, Matthias; Voßhall, Tobias; Diehl, Peter; Kučera, Pavel (International journal of environmental research and public health, 2021)
Reducing fuel consumption and thus CO2 emissions is one of the most urgent tasks of current research in the field of internal combustion engines. Water Injection has proven its benefits to increase power or optimize fuel consumption of passenger cars. This technology enables knock mitigation to either increase the engine power output or raise the compression ratio and efficiency while enabling λ = 1 operation in the complete engine map to meet future emission targets. Current systems have limited container capacity. It is necessary to refill the water tank regularly. This also means that we cannot get the benefits of an engine with a higher compression ratio. For this reason, the self-contained system was investigated. This article is a methodology for finding the right design of a self-contained water injection system, but also a vehicle test that proves the function.
Keywords: self-contained tank; Gasoline; automobily; výzkum; výfukové emise vozidel; Research; Water; exhaust condensate; water injection; benzin; Automobiles; EGR; compression ratio; voda; Vehicle Emissions